ANALISIS KEBUTUHAN SIM-PENDIDIKAN DAN RANCANGAN DESAIN PENGEMBANGAN DI SD NEGERI CILIBUR 01 - Sapii; Nur Aeni; Sutrisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital transformation in education requires elementary schools to manage academic, financial, infrastructure, and communication data effectively. This study aims to analyze the needs of a cloud-based Education Management Information System (EMIS) at SD Negeri Cilibur 01. The research employed a qualitative descriptive case study approach, using observation, interviews, and documentation. Findings indicate that data management is still conducted manually, leading to delays, duplication, and limited transparency. The needs analysis identified five essential modules: academic, staffing, finance, infrastructure, and communication. The proposed cloud-based EMIS blueprint consists of three stages: digitization, integration, and analytic portal. The implementation of this system is expected to enhance efficiency, accountability, and the quality of educational services. The study recommends teacher and staff training, local government policy support, and integration with the national education system.